2020
DOI: 10.1111/cup.13804
|View full text |Cite
|
Sign up to set email alerts
|

Atypical cells on reflectance confocal microscopy may not represent melanoma: A case of axillary pigmented extramammary Paget disease

Abstract: Pigmented extramammary Paget disease (PEMPD) is a rare intraepithelial carcinoma which can clinically resemble other pigmented neoplasms. Similarities to melanoma on dermoscopy, histopathology, and reflectance confocal microscopy (RCM) increase the risk of misdiagnosis and, consequently, mismanagement. Here, we describe a case of a 67-year-old African American woman with a large, pigmented axillary patch that exhibited features of melanoma on RCM, guiding the clinician to perform an excisional biopsy. While tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In particular, Paget cells occasionally exhibit cytoplasmic melanin granules, forming PMPD. Under the reflectance confocal microscopy, pagetoid cells (some with melanin pigment) and proliferative dendritic melanocytes could also be observed, which indicated that PMPD can mimic the feature of melanoma, increasing the risk of misdiagnosis ( 10 ). Nevertheless, histology could provide clues to differentiate these two disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Paget cells occasionally exhibit cytoplasmic melanin granules, forming PMPD. Under the reflectance confocal microscopy, pagetoid cells (some with melanin pigment) and proliferative dendritic melanocytes could also be observed, which indicated that PMPD can mimic the feature of melanoma, increasing the risk of misdiagnosis ( 10 ). Nevertheless, histology could provide clues to differentiate these two disorders.…”
Section: Discussionmentioning
confidence: 99%
“…RCM is a skin imaging technology that is rapidly developing in RCM has been reported as a diagnostic adjunct for mammary Paget disease and EMPD in several case reports and small studies (Chuchvara et al, 2020;Huang et al, 2019;Jang et al, 2016;Longo et al, 2007;Pan et al, 2012;Richtig et al, 2011). It was demonstrated that Paget cells appear as dark "holes" in granular layer, a bright circular center surrounded by a larger dark halo was shown in RCM (Huang et al, 2019), and the size of Paget cells was more than twice that of keratinocytes (Pan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One study explored the value of RCM in the diagnosis of EMPD, without considering differential diagnosis (Pan, Liang, Zhang, Lin, & Zheng, 2012). Several case reports found that RCM could be used to identify EMPD from several other diseases, such as melanoma (Chuchvara et al, 2020;Longo et al, 2007), squamous cell carcinoma (SCC) (Jang, Bae, Shin, & Lee, 2016), and mamillary eczema (Richtig, Ahlgrimm-Siess, Arzberger, & Hofmann-Wellenhof, 2011). Besides, it was also reported that RCM has the ability to diagnose and differentially diagnose inflammatory skin diseases, such as psoriasiform dermatitis, interface dermatitis, and spongiotic dermatitis (Agozzino, Gonzalez, & Ardigò, 2016).…”
Section: Introductionmentioning
confidence: 99%